2020
DOI: 10.1111/echo.14935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulmonary arterial stiffness in patients with cirrhosis: A prospective cohort study

Abstract: Introduction In the current literature, several studies show that PAS (pulmonary artery stiffness) is associated with RV (right ventricular) dysfunction, PAH (pulmonary arterial hypertension), and disease severity in subjects with structural cardiac disease, HIV (human immunodeficiency virus), and chronic lung disease. Hence, our main aim was to use PAS to show the early changes in the pulmonary vascular region in subjects with cirrhosis. Material and Methods In this prospective cross‐sectional study, 39 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…While there is no clear pathophysiologic explanation, early studies also reported isolated RV dysfunction in people living with HIV independent from pulmonary hypertension [21,22]. Moreover, an increased pulmonary arterial stiffness was observed in patients with HIV [23].…”
Section: Discussionmentioning
confidence: 99%
“…While there is no clear pathophysiologic explanation, early studies also reported isolated RV dysfunction in people living with HIV independent from pulmonary hypertension [21,22]. Moreover, an increased pulmonary arterial stiffness was observed in patients with HIV [23].…”
Section: Discussionmentioning
confidence: 99%
“…Öz et al showed that PAS might be helpful in the early detection of abnormalities in the pulmonary vascular bed even while RV function or sPAP levels were normal in cirrhotic patients. 14 Another study found that PAS values increased in polycystic ovarian syndrome patients, and it was associated with high Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) levels. 15 In the same study, it was reported that the same patient group had reduced RV-PA coupling, which was an indication of PA compliance that played a signi cant role in the etiology of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…RV‐PA coupling was calculated according to the following formulas: RV‐PA coupling(mm/mmHg) = TAPSE/MPAP (Prins et al, 2016). PAS (kHz/s) was calculated according to the following formula: PAS = MFS/AT PA (Abacioglu et al, 2021; Görgülü et al, 2003; Öz et al, 2021). Subsequently, the right superior pulmonary vein from the apical four‐chamber view was found by adjusting the position of the transducer, so that the pulmonary vein opening can be clearly displayed.…”
Section: Methodsmentioning
confidence: 99%
“…RV-PA coupling was calculated according to the following formulas: RV-PA coupling(mm/ mmHg) = TAPSE/MPAP (Prins et al, 2016). PAS (kHz/s) was calculated according to the following formula: PAS = MFS/AT PA (Abacioglu et al, 2021;Görgülü et al, 2003;Öz et al, 2021).…”
Section: Doppler Echocardiographymentioning
confidence: 99%